Puha költségvetési korlát, a szerződések kezelése és a notórius megbízhatatlanság - Gál, Róbert Iván (Szociológiai Szemle, 2024)
According to Fukuyama, the creation of confidence needed to co-operation belongs to that twenty per cent of social phenomena we are unable to account for by the terms of rational decisions. Therefore social scientists often define the phenomenon in question by the concepts of culture, socialisation, mentality, or habitus. Such explanations, however, become clumsy when they have to explain social change, particularly rapid changes. Whereas during the period between 1988 and 1993, studied by the paper, the reliability of contracts has significantly improved, the handling techniques of contracts have been transformed. How would it be possible to achieve such a rapid change in habitus, or mentality, how could re-socialisation be so fast? And why would these changes point particularly in the direction of the improvement of contractual discipline?In order to avoid the possible stumbling blocs, we have tried to drop explanations based on a certain constellation, the „it is just like this and not that” of preferences. We have construed such a model in which individual actions derive from the rational calculations o f the persons involved. The changes to be explained were not deducted from the changing preferences but we have attempted to find such environmental variables influencing the decisions of actors, the changes of which may have caused the changes in the behaviour of contracting parties and in the contracts themselves. This variable was found in the softness, or hardness of the budgetary constraint, that is in the presence, or lack of presence of a third actor behind the contracting parties, or, who can be utilised by them.